Magical Realism in Ahmad Sa'dawiy's Frankenstein fi Bagdad - Mahmudah Mahmudah (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2016)
This article discusses the use of magic realism as a literary device in the Iraqi novel Frankenstein fī Bagdād written by Aḥmad Sa‘dāwiy. The novel is set in the period of inter-ethnic conflict which arose after the American invasion of 2003. Hādī, the main character of the novel, ‘creates a monster’ namely Syismah from the corpses of the many bomb victims in Baghdad. The writer combines setting of the novel with belief of the Iraq people, horoscope practice, and magic, in mystical and illogical atmosphere. Given its magic realist qualities, the analysis draws on the approach of Wendy B. Faris. The article identifies five key elements from magic realism present in the novel, and discusses the relationship between these elements in order to better understand the social, ideological, and political context of the novel. The analysis shows that there are relationships between two worlds: death and life, human and ghost, physical and metaphysical, natural and supernatural.